Right and left ventricle native T1 mapping in systolic phase in patients with congenital heart disease. (March 2021) - Secchi, Francesco; Alì, Marco; Monti, Caterina B; Greiser, Andreas; Pluchinotta, Francesca R; Carminati, Mario; Sardanelli, Francesco
Background: T1 mapping is emerging as a powerful tool in cardiac magnetic resonance (CMR) to evaluate diffuse fibrosis. However, right ventricular (RV) T1 mapping proves difficult due to the limited wall thickness in diastolic phase. Several studies focused on systolic T1 mapping, albeit only on the left ventricle (LV). Purpose: To estimate intra- and inter-observer variability of native T1 (nT1) mapping of the RV, and its correlations with biventricular and pulmonary function in patients with congenital heart disease (CHD). Material and Methods: In this retrospective, observational, cross-sectional study we evaluated 36 patients with CHD, having undergone CMR on a 1.5-T scanner. LV and RV functional evaluations were performed. A native modified look-locker inversion recovery short-axis sequence was acquired in the systolic phase. Intra- and inter-reader reproducibility were reported as complement to 100% of the ratio between coefficient of reproducibility and mean. Spearman ρ and Mann–Whitney U -test were used to compare distributions. Results: Intra- and inter-reader reproducibility was 84% and 82%, respectively. Median nT1 was 1022 ms (interquartile range [IQR] 1108–972) for the RV and 947 ms (IQR 986–914) for the LV. Median RV–nT1 was 1016 ms (IQR 1090–1016) in patients with EDVI ≤100 mL/m 2 and 1100 ms (IQR 1113–1100) in patients with EDVI >100 mL/m 2 ( P = 0.049). A significant negative correlation was found between RV ejection fraction and RV–nT1 (ρ = −0.284, P = 0.046). Conclusion: Systolic RV-nT1 showed a high reproducibility and a negative correlation with RV ejection fraction, potentially reflecting an adaptation of the RV myocardium to pulmonary valve/conduit (dys)-function.